Etiologies and delirium rates of elderly ED patients with acutely altered mental status: a multicenter prospective study - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2017)
Objectives: Altered mental status (AMS) is a challenging diagnosis in older patients and has a large range of etiologies. The aim of this study was to investigate the nature of such etiologies for physicians to be better aware of AMS backgrounds and hence improve outcomes and mortality rates. Methods: This prospective observational study was conducted at 4 emergency departments. Patients 65 years and older who presented to the emergency department with acute AMS (<= 1 week), with symptoms ranging from comas and combativeness, were eligible for inclusion in this study. The outcomes, etiologies, Richmond Agitation and Sedation Scale scores, and the presence of delirium were recorded. Results: Among 822 older patients with AMS, infection (39.5%) and neurological diseases (36.5%) were the most common etiologies. The hospital admission and mortality rates were 73.7% (n= 606) and 24.7% (n= 203), respectively. The mortality rate rose if AMS persisted for more than 3 days. Delirium was observed in 55.7% of the patients; these individuals had higher durations of AMS than those without delirium (median, 24 hours; interquartile range, 3-48 hours; median 6 hours, interquartile range, 3-48 hours, respectively; P =.010). Notably, delirium was observed in more than two-thirds of neurological patients. Conclusions: The most common causes of AMS were infection and neurological diseases. Delirium was associated with AMS in nearly half the patients. Moreover, the rates of hospitalization and mortality remained high. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: EMERGENCY-DEPARTMENT PATIENTS; INTENSIVE-CARE-UNIT; OLDER PATIENTS; RELIABILITY; DIAGNOSIS; MORTALITY; VALIDITY; COMA